The Effects of Corona Pandemic (Covid 19) on the Exercise of Access to Justice : A Comparative Analytical Study - Mahmoud, Sayed; Mahmoud, Ahmed (Journal of Legal Sciences, 2023)
This study seeks to clarify the adequacy of the current legal texts - procedural and objective - to respond to our situation under Corona and whether it needs to modify or develop treatment for this general exceptional circumstance or to avoid it, and the appropriateness of the idea of force majeure or emergency circumstance or (the idea of foreign reason) to face the consequences or effects of Corona on the rules of litigation and the formation of the court and its jurisdiction and procedural appointments and litigation procedures and appeal and judgment and its implementation in order to maintain and implement the public order that interferes with the mechanisms and measures taken It is intended and has legal and judicial implications for the legal stay and the exceptions that are included. All this is done through an analytical, rooting and comparative approach to access alternatives and proposals in this regard.